Facile Synthesis of Mesoporous MoS2‐TiO2 Nanofibers for Ultrastable Lithium Ion Battery Anodes. Issue 3 (9th January 2015) - Zhuang, Wei; Li, Licheng; Zhu, Jiahua; An, Rong; Lu, Linghong; Lu, Xiaohua; Wu, Xinbing; Ying, Hanjie
Abstract TiO2 hybrid nanocomposites are promising electrode materials for lithium‐ion batteries because of the large specific capacity, excellent rate capability, and high cycling stability. We have developed an effective facile incipient wetness impregnation method that can be used to fabricate novel mesoporous MoS2–TiO2 fibrous nanocomposites. The MoS2–TiO2 nanocomposites exhibited notable electrochemical performance with a high capacity of 120 mA h g−1 at a rate of 40 C and long‐term, stable capacity of 124 mA h g−1 with a capacity retention of 75.2 % after 1000 cycles. These results suggest that the structure of mesoporous TiO2 nanofibers composited with a thin, uniform, well‐dispersed MoS2 layer improve the rate performance and cycling stability. Such good performance may be derived from the dispersed MoS2 layer, which accelerates the surface electrochemical reactions and offers a stable structure.